2018
DOI: 10.4103/1319-2442.235184
|View full text |Cite
|
Sign up to set email alerts
|

Nigella sativa prevented liver and renal tissue damage in lipopolysaccharide-treated rats

Abstract: Liver and renal dysfunction accompanying with the tissues' oxidative damage has been reported to occur during Inflammation. Nigella sativa has been well known for its antioxidant and anti-inflammatory effects. The aim of this study was to investigate preventive effects of N. sativa on liver and renal tissue damage in lipopolysaccharide (LPS) -treated rats. The rats were divided into five groups: (1) control; (2) LPS (1 mg/kg, IP, for 10 days), (3-5) N. sativa hydroethanolic extract (100, 200, or 400 mg/kg) bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Previous studies conducted on Nigella sativa (NS) oil and its main bioactive constituent TQ showed that they have both antioxidant and renoprotective properties in STZ-induced diabetes in the animal models and in ischemia-reperfusion-induced renal disorders [ 10 , 11 ]. In addition, NS and TQ were recently reported to have the potential to prevent renal tissue damage and fibrosis in lipopolysaccharide- (LPS-) treated rats through its antioxidant and anti-inflammatory effects [ 12 , 13 ]. It was reported that the hydroalcoholic extract of NS could protect the renal tissue against oxidative stress associated with neonatal and juvenile hypothyroidism in rats [ 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies conducted on Nigella sativa (NS) oil and its main bioactive constituent TQ showed that they have both antioxidant and renoprotective properties in STZ-induced diabetes in the animal models and in ischemia-reperfusion-induced renal disorders [ 10 , 11 ]. In addition, NS and TQ were recently reported to have the potential to prevent renal tissue damage and fibrosis in lipopolysaccharide- (LPS-) treated rats through its antioxidant and anti-inflammatory effects [ 12 , 13 ]. It was reported that the hydroalcoholic extract of NS could protect the renal tissue against oxidative stress associated with neonatal and juvenile hypothyroidism in rats [ 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…47 • Exerts therapeutic and anti-oxidant effects against lipopolysaccharides-induced inflammation in diabetic patients. 48…”
Section: Hepatoprotectivementioning
confidence: 99%
“… 47 Exerts therapeutic and anti-oxidant effects against lipopolysaccharides-induced inflammation in diabetic patients. 48 Antifibrotic effect Attenuates hepatic fibrosis. 49 Nutritional supplement Nigella sativa improves malnutrition associated with metabolic diseases, eg, Refsum’s disease.…”
Section: Prophetic Medicine Remedies As Promising Adjuvants For Treat...mentioning
confidence: 99%
“…There have been reports of renal impairment occurring alongside oxidative tissue damage when there is inflammation 37 . Chronic kidney disease's pathophysiological foundation includes OxS, apoptosis, and inflammation.…”
Section: Renal Tissue Antioxidantmentioning
confidence: 99%